THE EFFECTS OF LONG EXPOSURE TO SYNCHRONOUS ONLINE COURSES ON THE COURSE’S ENGAGEMENT OF INDUSTRIAL AND SYSTEMS ENGINEERING STUDENTS DURING THE COVID-19 PANDEMIC (Proceedings of the International Conference on Education, 2022)
After exposure to three semesters of synchronous online courses due to COVID-19 pandemic restrictions, higher education students faced negative effects in terms of motivation. To evaluate the impact of this long exposure to face-to-face online sessions in student’s motivation to be present and participate in class, an online survey was applied to Industrial and Systems Engineering students in a private university in Mexico at the end of each semester, beginning with the start of the COVID-19 pandemic and its restrictions preventing face-to-face class sessions. The survey included questions in a Likert scale for quantitative analysis and two open ended questions for qualitative analysis. A Two Sample T-test was conducted to identify significant differences in evaluations after time passed. The evaluations of different aspects, such as students' motivation to participate and be present in class showed a significant reduction between the first two semesters. Some results indicated the professors' ability to adapt the courses. The motivation to attend synchronous online sessions for mixed DFM courses (balancing practice and theory) decreased significantly between the first semester (Spring 2020) and the second semester (Fall 2020). Students' active participation during the mixed-course sessions changed significantly between Spring 2020 and Fall 2020, the latter having less participation. Notably, this demotivation was observed in the synchronous online courses.In qualitative analysis, answers were classified into categories for what  student’s considered valuable and what not and findings revealed demotivation for other activities that extend students' screen time exposure, such as readings, homework, requiring software and simulators, practices, and online teamwork sessions. This analysis provides recommendations for improving students' engagement, and participation. It considers immediate future scenarios, designing more effective courses for the "new normality" and unforeseen circumstances.
Keywords: higher education; educational innovation; burnout; Education during the pandemic; engagement